2020
DOI: 10.1161/jaha.119.014408
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Elevated Heart Rate Is an Important Predictor of Exercise‐Induced Troponin Elevation

Abstract: Background The precise mechanisms causing cardiac troponin ( cT n) increase after exercise remain to be determined. The aim of this study was to investigate the impact of heart rate (HR) on exercise‐induced cT n increase by using sports watch data from a large bicycle competition. Methods and Results Participants were recruited from NEEDED (North Sea Race … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…Also, a field study among 177 cyclists participating in a 91-km mountain bike race showed that the time spent performing high-intensity exercise (heart rate >150 bpm) was an independent predictor of postexercise cTnI and cTnT concentrations. 30 In aggregate, these data suggest that postexercise cTn elevations are related to overall cardiac workload, the product of both duration and intensity.…”
Section: Exercise-induced Cardiac Troponin Elevationsmentioning
confidence: 84%
“…Also, a field study among 177 cyclists participating in a 91-km mountain bike race showed that the time spent performing high-intensity exercise (heart rate >150 bpm) was an independent predictor of postexercise cTnI and cTnT concentrations. 30 In aggregate, these data suggest that postexercise cTn elevations are related to overall cardiac workload, the product of both duration and intensity.…”
Section: Exercise-induced Cardiac Troponin Elevationsmentioning
confidence: 84%
“…Third, the late elevation of creatine kinase and myoglobin from skeletal muscle after high-load, long duration exercise is mirrored by the cTnT and cTnI elevations observed in young athletes [17] , [38] . Participants in extreme races often develop troponin elevations that are ten times the assay specific cutoff's that become more prominent after long bouts of exercise [39] and is related to duration of elevated heart rates [40] . Most studies have not excluded necrotic events, but necrosis is unlikely to be the only release mechanism as most participants that develop troponin elevations are young and fit.…”
Section: Discussionmentioning
confidence: 99%
“…At similar average heart rates during exercise, hs-cTn changed more severely following intermittent exercise with higher maximal heart rates (Li et al, 2020 ). The duration of exercise above certain threshold heart rates therefore seemed to play an important role in hs-cTn elevation (Bjørkavoll-Bergseth et al, 2020 ), so more research on the effects of exercise intensity is obviously needed.…”
Section: Discussionmentioning
confidence: 99%